2009
DOI: 10.1002/zoo.20240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dilution degree of commercial nectar and provision of fruit on food, energy and nutrient intake in two rainbow lorikeet subspecies

Abstract: A feeding trial was performed on adult rainbow lorikeets of two subspecies: six green-naped lorikeets (Trichoglossus haematodus haematodus) and six red-breasted lorikeets (T. haematodus mitchellii). Throughout the entire trial, half of the birds from each subspecies had ad libitum access to water-diluted commercial nectar powder and drinking water only, whereas the other half also received ad libitum apple pieces. During three consecutive 14-d periods, the nectar powder was diluted to a different degree: 1:3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Comparable trials done on lorikeets in captivity, energy intake of T. haematodus (haematodus and mitchelli) varied between 765 and 987 kJ ME/kg MBW with the lowest energy intake being on the low “nectar” concentration treatment, which agrees with our results (Kalmar et al, ). Kalmar et al () used the same estimation equations for determination of ME as Häbich (), whereas we used the digestibility coefficients in the results of Häbich (). This explains why our results are in the lower end of Kalmar et al ()’s range.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Comparable trials done on lorikeets in captivity, energy intake of T. haematodus (haematodus and mitchelli) varied between 765 and 987 kJ ME/kg MBW with the lowest energy intake being on the low “nectar” concentration treatment, which agrees with our results (Kalmar et al, ). Kalmar et al () used the same estimation equations for determination of ME as Häbich (), whereas we used the digestibility coefficients in the results of Häbich (). This explains why our results are in the lower end of Kalmar et al ()’s range.…”
Section: Discussionsupporting
confidence: 92%
“…Kalmar et al () used the same estimation equations for determination of ME as Häbich (), whereas we used the digestibility coefficients in the results of Häbich (). This explains why our results are in the lower end of Kalmar et al ()’s range. Birds usually fed on “energy maintenance” (Klasing, ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, even though consumption of drinking water was not affected by availability of fruit, birds ingested more fluid and thus volume when fruit was available. Kalmar et al. (2009) showed a negative relation between moisture content of nectar and voluntary energy intake in lorikeets, suggesting a saturation effect on account of energy dilution by water.…”
Section: Discussionmentioning
confidence: 94%
“…This could be associated with their specifi c eating habits. Kalmar et al (2000), Tomiška (2011) andVašíček (2004) suggested that being nectar-eating birds, the lories have no need to pick the seeds on the ground. They only come down to the ground to collect some pieces of vegetation and grasses which they use for nest-building (Buckley, 1968).…”
Section: Resultsmentioning
confidence: 99%